Порівняльне дослідження впливу складу та фізичних полів на структуру і теплофізичні властивості уретановмісних полімерних композитів - Глієва, Г.Є.; Віленський, В.О.; Керча, Ю.Ю.; Гончаренко, Л.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The comparative study the influence of the content and constant magnetic and electrical fields upon the structure and thermophysical properties of composites of incompatible polymers is fulfilled. Peculiarities of the action of the given factors upon the modification of a polymer system of cellulose acetate butyrate and segmented polyurethane are shown.